PROSPECTS ON TITANIUM BIOMATERIALS - Madalina Simona BALTATU; Petrica VIZUREANU; Andrei Victor SANDU; Iustinian BALTATU; Doru Dumitru BURDUHOS-NERGIS; Marcelin BENCHEA (European Journal of Materials Science and Engineering, 2023)
Biomaterials are substances that have been engineered to interact with biological systems for a medical purpose, either a therapeutic or diagnostic one. Biomaterials have a rich history of evolution, as they have continuously transformed from simple inert substances to complex, interactive materials, designed to communicate with biological systems and promote tissue regeneration and healing. Titanium, due to its excellent biocompatibility, corrosion resistance, and mechanical properties, has established its place as one of the most used biomaterials, particularly in orthopedics and dental applications. This article provides an overview of titanium as a biomaterial, highlighting its properties, applications, and recent advancements.